Evaluation and its link with institutional responsibility for learning in basic education - Maruri Arévalo, Susana Magaly (Atenas, 2016)
The purpose of this study is to systematize an interpretation of the categories of institutional responsibility regarding the assessment, which allows knowing the operation of the measurement as educational system and resizes use in improving basic school in Ecuador. School evaluation sets a frame of meanings and practices that are mediated by institutional responsibility in learning, in this sense basic education set many dimensions according to the rhythms and styles of learning school, being unveiled effectiveness or failure by the process directing educational evaluation feedback.